Infiltration to surface runoff ratio estimations with surface geophysics in the topsoil of loess deposits (Zala region, Hungary) - Müller, Imre (GEORGIKON FOR AGRICULTURE, 2008)
Three geophysical methods were applied to estimate infiltration to surface runoff ratio of topsoils in Loess environment. The test field (Tilaj, Zala county), divided in fallow land and plough-land, present similar magnetic susceptibilities and seismic velocities, but a significant difference is showed up by electrical resistivities, with a short Wenner array (a = 0.5m). Due to the biological activities, the fallow land remain porous and permeable, thus favour good infiltrations. In this area the distribution of resistivities is heterogeneous and varies between 58 and 178 Ohmm. In the plough-land, also treated with chemicals, the biological activities diminish in the topsoil, producing clogging, and reduction of porosity and decrease of permeability. Surface runoff and erosion appears. In this part of the test field resistivities are low, 23–40 Ohmm and homogeneously distributed.